2013
DOI: 10.1371/journal.pone.0054994
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of the 5-Hydroxytryptamine Transporter Gene-Linked Promoter Region Polymorphism on Susceptibility to Lifelong Premature Ejaculation

Abstract: ObjectivePremature ejaculation (PE) has been reported as the most common male sexual dysfunction with global prevalence rates estimated at approximately 30%. The neurobiogenesis of ejaculation is very complex and involves the serotoninergic (5-hydroxytryptamine, 5-HT) system. Recently, genetic polymorphisms located on SLC6A4 gene codifying for 5-HT transporter (5-HTT), the major regulator of serotonic neurotransmission, have been linked with the pathogenesis and risk of PE. Apparently studies of this type of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
1
31
3
Order By: Relevance
“…In accordance with this prediction, one study found that polymorphism in the serotonin transporter promoter region (5-HTTLPR) is associated with ejaculation latency time (Janssen et al 2009). A meta-analysis found significant associations between the risk of premature ejaculation and 5-HTTLPR polymorphism (Zhu et al 2013). Furthermore, another study found that polymorphism in the dopamine transporter gene (DAT1) is associated with premature ejaculation (Santilla et al 2010see also Safarinejad 2011.…”
Section: Predictions and Evidencementioning
confidence: 87%
“…In accordance with this prediction, one study found that polymorphism in the serotonin transporter promoter region (5-HTTLPR) is associated with ejaculation latency time (Janssen et al 2009). A meta-analysis found significant associations between the risk of premature ejaculation and 5-HTTLPR polymorphism (Zhu et al 2013). Furthermore, another study found that polymorphism in the dopamine transporter gene (DAT1) is associated with premature ejaculation (Santilla et al 2010see also Safarinejad 2011.…”
Section: Predictions and Evidencementioning
confidence: 87%
“…With the also lower OR found in LL versus SS genotype frequencies in all Caucasian patients versus controls (OR = 0.88; CI 0.80–0.98), and lower OR also found in LL+LS versus SS genotype frequencies in Caucasian patients versus controls (OR = 0.83; CI 0.70–1.00), Zhu et al [13] interpreted these results as that SS genotype and/or S-allele are risk factors of lifelong PE. And therefore they concluded that LL genotype and/or L-allele might be protecting factors for lifelong PE.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, as Zhu et al [13] have pooled the ORs of 5 (Caucasian) studies, including the two studies not-in-HWE (Safarinejad and Ozbek), they erroneously calculated a low OR for all five of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the effectiveness of the serotoninergic drugs in PE, researchers focused on the serotoninergic genes as the promoter region of the 5-HT transporter gene, which has been the most extensively studied (91)(92)(93)(94). Positive associations equal negative associations, and the issue should be considered at least controversial.…”
Section: Risk Factors the Role Of The Geneticsmentioning
confidence: 99%
“…However, the same association was reported by others but in the opposite direction (92,95). Even a metaanalysis on these data (93) has been criticized (96).…”
Section: Risk Factors the Role Of The Geneticsmentioning
confidence: 99%